KADAR SERAT KASAR DAN KECERNAAN SECARA IN VITRO JERAMI KEDELAI YANG DITANAM DENGAN PERLAKUAN PENYIRAMAN AIR LAUT DAN MULSA ECENG GONDOK - Ghina Meriyana Dewi; Surahmanto Surahmanto; E. Fuskhah (JURNAL LITBANG PROVINSI JAWA TENGAH, 2015)
This study aims to analyze the crude fiber content, in vitro dry matter digestibility and organic matter digestibility of soybean straw were planted with watering sea water and water hyacinth mulch. Research using completely randomized design with a 4x2 factorial pattern 4 replications. The first factor is the level of sea water sprinkling consisting of L0 (without seawater/fresh water), L1 (seawater EC 1 mmhos/cm), L2 (sea water EC 1.5 mmhos/cm), and L3 (seawater EC 2 mmhos/cm). The second factor is the doze of water hyacinth mulch which consists of M1 (without mulch) and M2 (water hyacinth mulch doze of 4 tons/ha), Data analysis of variance (ANOVA) and to know the difference between treatments continued with Duncan Multiple Range Test (DMRT). The results showed that there was no significant interaction between sea water levels and doze of water hyacinth mulch on crude fiber content, KcBK and KcBO of soybean straw. The conclusion of this study is the treatment of watering with sea water 1.5 mmhos/cm gives the best results in soybean straw on crude fiber content of 44.79%, dry matter digestibility of 63.92%, and organic matter digestibility of 58.87%.